2022
DOI: 10.1038/s41699-022-00342-4
|View full text |Cite
|
Sign up to set email alerts
|

Layer-dependent Schottky contact at van der Waals interfaces: V-doped WSe2 on graphene

Abstract: Contacting two-dimensional (2D) semiconductors with van der Waals semimetals significantly reduces the contact resistance and Fermi level pinning due to defect-free interfaces. However, depending on the band alignment, a Schottky barrier remains. Here we study the evolution of the valence and conduction band edges in pristine and heavily vanadium (0.44%), i.e., p-type, doped epitaxial WSe2 on quasi-freestanding graphene (QFEG) on silicon carbide as a function of thickness. We find that with increasing number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…It is worth noting that in a recent STM study performed on the same material system no subsurface vanadium dopants were observed. The clear visibility of buried impurities in cAFM is consistent with our model where tunneling is assumed to occur primarily between the tip and graphite substrate with impurities acting only as a local perturbation to the tunnel barrier.…”
Section: Resultsmentioning
confidence: 83%
“…It is worth noting that in a recent STM study performed on the same material system no subsurface vanadium dopants were observed. The clear visibility of buried impurities in cAFM is consistent with our model where tunneling is assumed to occur primarily between the tip and graphite substrate with impurities acting only as a local perturbation to the tunnel barrier.…”
Section: Resultsmentioning
confidence: 83%
“…21,63−66 Very recently, Stolz et al have reported that vanadium is a p-type dopant for WSe 2 synthesized by metalorganic chemical vapor deposition. 67 It has been highlighted that the E F pinning and Schottky contact behavior show up upon the number of WSe 2 layers exceeding 2 due to the change of the band structure. 67 This affirms that the impurity dopant is one of the origins of E F pinning at the metal/TMD interface.…”
Section: Resultsmentioning
confidence: 99%
“…67 It has been highlighted that the E F pinning and Schottky contact behavior show up upon the number of WSe 2 layers exceeding 2 due to the change of the band structure. 67 This affirms that the impurity dopant is one of the origins of E F pinning at the metal/TMD interface. The E F of Ni/WSe 2 is pinned at 4.92 eV which is close to the valence band edge of the WSe 2 bulk crystal (5.33 eV).…”
Section: Resultsmentioning
confidence: 99%
“…However, the same work reports a (Mo:Re)­S 2 ML alloy, whose metastability window is small and high in energy (see Figure a and SI Figure S2). Another recent report characterizes (V:Mo)­S 2 MLs experimentally, which is also a TM pair likely to mix according to our analysis. The first example mentioned above, (Mo:W)­S 2 (green lines in Figure a), has also been realized in experiments. , Finally, V-doped WSe 2 and (Mo:W)­Se 2 alloys have been recently synthesized as non-MoS 2 -based examples that are both indicated as likely miscible alloys in Figure b.…”
Section: Optimal Prototypes For Alloysmentioning
confidence: 90%
“…The first example mentioned above, (Mo:W)S 2 (green lines in Figure 4 a), has also been realized in experiments. 16 , 39 Finally, V-doped WSe 2 and (Mo:W)Se 2 alloys have been recently synthesized 40 42 as non-MoS 2 -based examples that are both indicated as likely miscible alloys in Figure 4 b.…”
Section: Optimal Prototypes For Alloysmentioning
confidence: 99%